2003
DOI: 10.1577/1548-8659(2003)132<0299:eimoff>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Electroshocking-Induced Mortality of Four Fish Species during Posthatching Development

Abstract: Immediate mortality of electroshocked fish was related to the stage of development after hatching. Larvae and juveniles of four species of fish were exposed to homogeneous voltage gradients (2-16 V/cm) of 60-Hz pulsed DC in water having an ambient conductivity of 100 S/ cm. Recently hatched fish and fish older than 100 d did not die after electroshocking. The developmental period most susceptible to electroshocking-induced mortality was near the time of transformation from larvae to juveniles for all four spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Delayed mortality is low (Ͻ10%) in most studies (Barrett and Grossman 1988;Habera et al 1996;Ruppert and Muth 1997;Cook et al 1998). In a previous paper, we reported that electroshocked channel catfish that were alive after 1 h did not die during the following 5 d, even though immediate mortality was 68% (Henry et al 2003a).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Delayed mortality is low (Ͻ10%) in most studies (Barrett and Grossman 1988;Habera et al 1996;Ruppert and Muth 1997;Cook et al 1998). In a previous paper, we reported that electroshocked channel catfish that were alive after 1 h did not die during the following 5 d, even though immediate mortality was 68% (Henry et al 2003a).…”
Section: Discussionmentioning
confidence: 89%
“…However, except for a comparison of two species by Whaley et al (1978), multiple-species comparisons of mortality after exposure to homogeneous electric fields have not been conducted. Laboratory experiments with homogeneous electric fields are useful for predicting the fish mortality caused by field electrofishing (Henry et al 2003a) and are appropriate for multiple-species comparisons of electrofishing-induced mortality.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Electrofishing can, however, be lethal or injurious to collected fishes (e.g., BardygulaNonn et al 1995;Dalbey et al 1996;Dwyer et al 2001;Snyder 2003;Dolan and Miranda 2004;Schreer et al 2004) or their offspring (e.g., Dwyer et al 1993;Dwyer and Erdahl 1995;Henry et al 2003;Bohl et al 2009). A few studies have examined nonlethal effects of electrofishing practices and found decreased fish feeding and growth rates (Gatz et al 1986;Gatz and Adams 1987;Dalbey et al 1996), increased susceptibility to predation , and increased nest abandonment in brood-guarding species (Siepker et al 2006b).…”
mentioning
confidence: 99%